A Comparative Analysis of the Functions and Roles of Reserve Bank of India and Federal Reserve System of the United States - Asif, Mohd (Journal of Global Economy, Business and Finance, 2025)
This article presents a comprehensive comparison of the Reserve Bank of India RBI and the Federal Reserve System FRS of the United States, focusing on their historical origins, functions, and roles. It examines how RBIs history is rooted in the consolidation of presidency town banks, while FRS emerged in response to banking panics and financial instability. The article delves into the multifaceted functions of both central banks, emphasizing RBIs wide range of policy tools, its extensive payment systems, and its focus on financial inclusion and literacy. It evaluates the modes of payment facilitated by each institution and highlights RBIs utilization of technology to offer diverse payment options. Furthermore, the article compares the charges and responsibilities associated with currency management in both systems. In conclusion, it underscores the significance of RBIs comprehensive role in the Indian economy and its proactive approach to policy implementation, providing valuable insights into the strengths and weaknesses of both central banks.